TRANSLATIONS OF THE NOVEL JANE EYRE BY C.BRONTE - Belova K.A; Karbozova Gulnara Kumisbekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article made an attempt of linguistic analysis of translations of the novel by Sh. Bronte “Jain Eyre. A comparison of several translations of the novel is carried out with an emphasis on their stylistic features, as well as their comparison with the original. The paper also describes the meaning of the linguistic personality for the literary text of the translation. The influence of a linguistic personality, which is the national and cultural prototype of a speaker of a certain language, is also found in the presented translations of Charlotte Bronte’s novel Jane Eyre.